(untitled) - Baron, Robert A. (Australia, 2005)
Entrepreneurship texts may, understandably, be viewed with some suspicion, as being nothing more than common sense dressed-up, and nothing unique or innovative. But Baron and Shane have attempted something new. Baron and Shane focus on the entrepreneurial process as it moves through several distinct phases: (1) generating ideas and recognizing opportunities, (2) assembling resources, (3) launching the new venture, (4) building success, and (5) harvesting the rewards. At each stage, they analyze these processes along three dimensions, examining individual, group, and societal contexts. Accessible and rich in examples, Baron and Shane gain the upper hand by fusing concepts, theory, and research with the supporting pedagogy.
Keywords: Entrepreneurship,New business enterprises